2018
DOI: 10.1080/13696998.2018.1434182
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of costs and outcomes of dapagliflozin with other glucose-lowering therapy classes added to metformin using a short-term cost-effectiveness model in the US setting

Abstract: This analysis showed that DAPA was cost-saving compared with GLP-1RA and DPP-4i, and cost-effective compared with SU and TZD in the US setting over 1 year. Furthermore, the results suggest that, among the four composite clinical end-points, change in weight and SBP had an impact on cost-effectiveness results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 32 publications
1
36
1
Order By: Relevance
“…It found that SGLT2i users experienced lower total medical costs compared with GLP-1RA and DPP-4i users. 17 In contrast, our study found that compared with prevalent DPP-4i users SGLT2i and GLP-1RA switchers experienced no difference in medical costs. This difference could be attributed to our focus on those who switched between drug classes rather than focusing solely on new users.…”
Section: Health Care Utilizationcontrasting
confidence: 66%
“…It found that SGLT2i users experienced lower total medical costs compared with GLP-1RA and DPP-4i users. 17 In contrast, our study found that compared with prevalent DPP-4i users SGLT2i and GLP-1RA switchers experienced no difference in medical costs. This difference could be attributed to our focus on those who switched between drug classes rather than focusing solely on new users.…”
Section: Health Care Utilizationcontrasting
confidence: 66%
“…In a cost-effectiveness model of DAPA compared with DPP-4 inhibitors in the United States, DAPA was found to be cost-saving. 26 The annual medical costs for patients on DAPA were $1119 lower than those on a DPP-4 inhibitor, with the difference in costs mainly attributable to weight change ($860). Similarly, in a UK population of patients on metformin, the addition of DAPA was shown to be a cost-effective treatment option, particularly because of the positive effect on weight loss, compared with the addition of a DPP-4 inhibitor.…”
Section: Discussionmentioning
confidence: 98%
“…Although peer‐reviewed studies with a head‐to‐head comparison of DAPA and SITA are lacking, several studies have found DAPA to be a cost‐effective approach to T2D treatment when compared with DPP‐4 inhibitors. In a cost‐effectiveness model of DAPA compared with DPP‐4 inhibitors in the United States, DAPA was found to be cost‐saving . The annual medical costs for patients on DAPA were $1119 lower than those on a DPP‐4 inhibitor, with the difference in costs mainly attributable to weight change ($860).…”
Section: Discussionmentioning
confidence: 99%
“…Previous economic evaluations have provided evidence supporting the cost-effectiveness of dapagliflozin as a monotherapy, dual therapy or triple therapy compared to other antidiabetes therapies for managing T2DM. For example, on a background insulin regime, dapagliflozin was cost-effective compared to insulin alone, 28 on a background of metformin, dapagliflozin was cost-effective when compared to sulphonylureas, [29][30][31][32][33] thiazolidinediones 29 and dipeptidyl peptidase-4 (DPP-4) inhibitors, 33,34 and on a background of metformin and sulphonylureas, dapagliflozin was cost-effective compared to a dipeptidyl peptidase-4 inhibitor. 35 Dapagliflozin monotherapy was cost-effective compared to glimepiride, acarbose and DPP-4 inhibitor monotherapy in individuals with T2DM receiving no other antidiabetes therapy.…”
Section: Introductionmentioning
confidence: 99%